Clinical, radiographic and patient-centered outcomes after use of enamel matrix proteins for the treatment of intrabony defects in patients with aggressive periodontitis: A 12-month multicenter clinical trial - Fileto Mazzonetto, Ana Livia; Casarin, Renato Correa Viana; Santamaria, Mauro Pedrine [UNESP]; Andere, Naira Maria Rebelatto Bechara [UNESP]; Araujo, Cassia Fernandes [UNESP]; Videira Clima da Silva, Rafaela; Purisaca, Javier Eduardo Vivanco; Sallum, Enilson Antonio; Sallum, Antonio Wilson (Wiley-Blackwell, 2020)
Background The aim of this study was to evaluate the clinical, radiographic and patient-centered results of enamel matrix derivative (EMD) therapy in intrabony defects in aggressive periodontitis (AgP) patients and compare them with those in chronic periodontitis (CP) patients. Methods Sixty intrabony defects in AgP and CP patients associated with >= 6 mm residual probing pocket depth (PPD) were included and randomly assigned to one of three groups: AgP+CS (conservative surgery) (n = 20); AgP+CS/EMD (n = 20); CP+CS/EMD (n = 20). Clinical parameters were measured at baseline and after 6 and 12 months. Defect resolution (DR) and bone filling (BF) were used for radiographic analysis. The quality of life was recorded at baseline and 6 months using OHIP-14 and VAS scale in the early post-therapy period. Results PPD and relative clinical attachment level (rCAL) improved for all groups during follow-up (P <= 0.05), and AgP+CS/EMD presented a higher rCAL gain (2.4 +/- 1.0 mm) when compared to AgP control patients (1.6 +/- 1.6 mm, P <= 0.05) after 12 months. No difference was observed between AgP+CS/EMD and CP+CS/EMD groups (P > 0.05). No radiographic differences were observed among groups at any time point (P > 0.05). All the groups reported a positive impact on OHIP-14 total score, without differences among them. Conclusions EMD therapy of intrabony defects promotes additional benefits in AgP patients, presenting a similar regeneration rate compared to CP patients, and has proven to be a viable therapy for the treatment of individuals with AgP.
Keywords: aggressive periodontitis; alveolar bone loss; chronic periodontitis; enamel matrix proteins